The influence of the stress factor in the legal practice - Sandu, Mihaela Luminita; Călin, Mariana Floricica; Dragomir, Rodica (Technium Social Sciences Journal, 2021)
Along with well known sources, we observe, for the modern person, that the work environment is a stress source who can contribute to the individual life quality deterioration. Professional stress, like it’s called in the law literature, is the stress generated from activities of work place and from the environment in which those activities occur. This type of stress can generate a multitude of atypical manifestations in a person and can have different durations correlated with the stress factors intensity. Maintaining the effects of the stress factors for long period of time can favor the somatic illnesses or even the organic ones. The explicit recommendation of specialists is to identify the most significant stress factors at the work place then take appropriate action to eradicate their causes, or, when possible to limit their effects. The law is a liberal professional, serving justice. So it’s a fact that without it as part of the judicial system, justice cannot prevail in an effective manner. Even if it’s essential to the judicial system, the law is internal to a dramatic decorum, open to threats. We cannot question the high degree of professional stress that is laid upon the members of this practice, and even the young attorneys at the beginning of their careers, who just graduated and have high dreams and strive to excel professionally, are at risk. Regrettably, with the beginning of the practice their dreams slowly dissipate, in the existential void, because of the long wait at the courthouse and the disappointment that deciding parties (judges and prosecutors) of the justice scene are imposing and impedes upon the justice spirit of the young attorneys.